Low temperature selective oxidation of methane to methanol using titania supported gold palladium copper catalysts. Issue 10 (24th December 2015) - Ab Rahim, Mohd Hasbi; Armstrong, Robert D.; Hammond, Ceri; Dimitratos, Nikolaos; Freakley, Simon J.; Forde, Michael M.; Morgan, David J.; Lalev, Georgi; Jenkins, Robert L.; Lopez-Sanchez, Jose Antonio; Taylor, Stuart H.; Hutchings, Graham J.
Abstract : Selective oxidation of methane using AuPdCu/TiO2 catalysts. Abstract : The selective oxidation of methane to methanol has been studied using trimetallic AuPdCu/TiO2 catalysts prepared by incipient wetness impregnation. They are able to catalyse the selective oxidation of methane to methanol under mild aqueous reaction conditions using H2 O2 as the oxidant. When compared with bimetallic, Au–Pd/TiO2 analogues, the new trimetallic catalysts present productivities which are up to 5 times greater under the same test conditions, and this is coupled with methanol selectivity of up to 83%. Characterisation shows that whilst Au–Pd is present as Au-core–Pd-shell nanoparticles, copper is present as either Cu or Cu2 O in <5 nm particles.